Keeping the balance - importance of balanced hippocampal neural activity for attention and memory - Gwilt, Miriam (2021)
Hippocampal neural disinhibition, i.e. decreased GABAergic control, has been implicated in neuropsychiatric disorders, including schizophrenia and age related cognitive decline, and cognitive impairments associated with these conditions. Previous work within our lab has demonstrated that infusion of the GABA-A antagonist picrotoxin into the ventral hippocampus causes marked increases in local multi-unit activity in anaesthetised rats, and causes both memory and attentional deficits akin to those seen in patients with schizophrenia and age-related cognitive decline (McGarrity et al. 2017). Alterations in normal neuronal oscillations are often seen in such clinical conditions, however the underlying pathology leading to such changes is still largely unknown (Schnitzler and Gross, 2005; Ulhaas and Singer, 2015). Furthermore, current pharmacological treatments for such disorders are limited in efficacy and, this leaves a large impact on patients (Maric et al. 2016; Breier 2005). Recently, the second-generation anti-epileptic drug levetiracetam has shown promise, at low doses, for ameliorating cognitive impairments related to hippocampal hyperactivity in both rodents and patients (Haberman et al. 2017; Koh et al. 2010, Bakker et al. 2012). Therefore, our two main aims were to assess the impact of our hippocampal disinhibition model on oscillatory activity within the brain, and to determine if low doses of levetiracetam are able to alleviate the neuro-behavioural impact of hippocampal disinhibition. First, we analysed the hippocampal local field potential (LFP) data from within the vicinity of the infusion site, which was recorded in conjunction with the previously published multi-unit data in anesthetised rats (McGarrity et al. 2017). To this end, we developed a novel semi-automated routine to separate three distinct LFP states seen under anaesthesia (Burst, Suppression, and Continuous), so that frequency analysis could be run without interference from state-specific properties (see Chapter 2 for details). Overall, we showed that hippocampal picrotoxin infusion caused an increase in theta power, tended to decrease high beta/low gamma power, and decreased high beta/low gamma connectivity (Chapter 2). In a further study, we examined the impact of hippocampal disinhibition on both the hippocampal LFP, frontal electroencephalogram (EEG) and heart rate variability (HRV) in unanaesthetised rats, by combining our hippocampal picrotoxin infusions with a telemetric-EEG (tEEG) protocol used by our industry partners at Boehringer Ingelheim (Chapter 3). These data revealed that, contrasting with our anaesthetised recordings (Chapter 2), hippocampal disinhibition had no effect on hippocampal theta power, but decreased hippocampal high beta/low gamma LFP power, confirming the trend seen previously. We saw limited effects on both the frontal EEG and the HRV. Overall, our studies assessing the oscillatory changes within the hippocampus after hippocampal disinhibition reveal a consistent decrease of power in the high beta/low gamma frequencies, which may be relevant to findings in schizophrenia and mild cognitive decline (Schnitzler and Gross, 2005). Secondly, to see if levetiracetam could ameliorate the neuro-cognitive impact of hippocampal disinhibition, we examined if systemic levetiracetam treatment could ameliorate the electrophysiological and some of the cognitive/behavioural effects caused by hippocampal disinhibition (Chapters 4-6). Initially, using multi-unit recordings under anaesthesia, we replicated previous findings (McGarrity et al., 2017) that hippocampal picrotoxin (150ng) enhances hippocampal burst firing. Levetiracetam selectively attenuated the increased burst duration at 10mg/kg (i.p.), but not 50mg/kg; 50mg/kg slightly reduced the peak frequency in bursts under baseline conditions (Chapter 4). Furthermore, 10mg/kg, but not 50mg/kg, ameliorated the decreased high beta/low gamma hippocampal LFP power induced by hippocampal disinhibition (Chapter 5). Based on these findings, we used 10mg/kg for the behavioural studies. We replicated previous findings (Bast et al., 2001; McGarrity et al., 2017) of increased locomotor activity in the open field and decreased search preference in the DMP watermaze task following hippocampal picrotoxin infusion. Levetiracetam (10mg/kg) numerically attenuated both locomotor hyperactivity and search preference in the DMP watermaze, although these beneficial effects failed to achieve criteria of statistical significance (Chapter 6). Overall, a low dose (10 mg/kg) of levetiracetam showed a trend towards ameliorating electrophysiological changes caused by hippocampal disinhibition; however, this was not sufficient to ameliorate the memory impairments and locomotor hyperactivity associated with hippocampal disinhibition. We showed that hippocampal disinhibition causes a local decrease in high beta/low gamma frequencies in both anesthetised and unanaesthetised rats, and an increase in theta frequencies of anaesthetised rats only. Furthermore, levetiracetam 10mg/kg was able to restore normal high beta/low gamma frequencies, and the burst duration multi-unit parameter, with limited ameliorative effect on locomotor hyperactivity and memory impairment in the DMP watermaze.